Estratificación pronóstica de pacientes con Leucemia Mieloide Crónica mediante la cuantificación por PCR real time de los niveles de transcripto de BCR-ABL1 - Zaffanella, María Belén (2019)
The treatment of chronic myeloid leukemia (CML) has changed radically in recent decades thanks to the introduction of tyrosine kinase inhibitors (ITK). Imatinib was the first inhibitor used and then the second and third generation were incorporated (eg Nilotinib, Dasatinib and Ponatinib).\nThanks to these molecularly targeted therapies, the majority of patients with CML, treated in the chronic phase of the disease, reach the complete cytogenetic response (CCR) after one year of treatment. However, even with CCR, the bone marrow can still contain a significant number of leukemic cells. For this reason it was necessary to implement quantitative real-time PCR (qRT-PCR) that allows to measure, with a higher sensitivity, the levels of BCR-ABL1 chimeric transcript in peripheral blood.\nFor the measurement of transcripts of BCR-ABL1, the International Scale represents a practical method to be able to compare the results of the qRT-PCR obtained in different laboratories; for this purpose, it is necessary for each laboratory to calculate a specific conversion factor (FC), using reference standards. From these calibrators, we obtained our FC to express the harmonized results at the international scale. Then, through the harmonized methodology, 191 peripheral blood samples anticoagulated with EDTA from 180 patients with a previous diagnosis of CML were studied.\nIn this thesis work, the level of molecular response reached is described according to the type of treatment and time. As a significant result, we found that although there is no significant difference between taking Imatinib or a generic one to achieve a greater molecular response, we saw that there is a tendency for Gleevec to be more effective over generics in achieving a deep molecular response. When we compared first and second generation inhibitors, we saw that Nilotinib has more impact to reach the deep molecular response than the larger molecular response, compared with Imatinib.\nFinally, this work shows the procedure and the complexity of harmonizing a molecular biology laboratory at the international scale for the measurement of BCR-ABL1 levels in peripheral blood, for patients with CML. However, this harmonization is a key step to be able to compare the results between laboratories, and at different times of treatment; In addition to these values corrected by the FC, the results acquire prognostic value, therefore they are useful for the doctor to make accurate clinical decisions, according to the international guidelines.